2022
DOI: 10.1021/acsami.1c17998
|View full text |Cite
|
Sign up to set email alerts
|

Steering Hydrocarbon Selectivity in CO2 Electroreduction over Soft-Landed CuOx Nanoparticle-Functionalized Gas Diffusion Electrodes

Abstract: The use of physical vapor deposition methods in the fabrication of catalyst layers holds promise for enhancing the efficiency of future carbon capture and utilization processes such as the CO2 reduction reaction (CO2RR). Following that line of research, we report in this work the application of a sputter gas aggregation source (SGAS) and a multiple ion cluster source type apparatus, for the controlled synthesis of CuO x nanoparticles (NPs) atop gas diffusion electrodes. By varying the mass loading, we achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…In comparison to the recently published electromethanation of CO 2 (Figure a), Cu–DCD 40 demonstrates high selectivity (FE) and activity (partial current density) of electromethanation. , To evaluate the stability of the as-prepared catalyst, “pause electrolysis” to suppress the carbonate issue is adopted in this work . The pause electrolysis is shown in Figure b.…”
Section: Resultsmentioning
confidence: 98%
“…In comparison to the recently published electromethanation of CO 2 (Figure a), Cu–DCD 40 demonstrates high selectivity (FE) and activity (partial current density) of electromethanation. , To evaluate the stability of the as-prepared catalyst, “pause electrolysis” to suppress the carbonate issue is adopted in this work . The pause electrolysis is shown in Figure b.…”
Section: Resultsmentioning
confidence: 98%
“…[11] Modification is an effective approach toward improving the performance of electrodes given that it changes the physical and chemical properties to provide for better bioelectrocatalyst attachment and electron transfer. Although novel electrodebased platforms, such as gas diffusion electrodes, [41] carbonbased foams, [42] and electrospun carbon nanofibers, [43] have been developed to meet the requirements of various applications, many need to be improved before practical use. In addition, thin coatings of silver (Ag), [44,45] and silicon dioxide (SiO 2 ) [9] effectively improve the interactive interface and reduce the activation energy threshold of electron transfer.…”
Section: Metallic Nanoparticle Platformsmentioning
confidence: 99%
“…This enabled higher partial current densities toward value‐added C 2+ products, and also shifted their selectivity. In situ oxidation for forming CuO x NP films with various mass loadings onto the GDLs as electrodes for CO 2 RR was reported by Deams et al [ 35 ] A sputter gas aggregation source together with a multiple ion cluster source‐type apparatus was employed. This demonstrated the distinct advantage of simultaneously control of the thickness/areal density, as well as the oxidation state of the as‐formed CuO x film layer during electrode preparation.…”
Section: Structures Design Of Electrodes For Co2rrmentioning
confidence: 99%
“…Furthermore, other advanced strategies have also been explored for the fabrication of CO 2 RR electrodes; however, they are still at an initial state, such as 3D printing, and in situ oxidation. [34,35] For example, by applying 3D printing technique, Wicks et al [34] reported the fabrication of a porous fluoropolymer as the base GDL, which was further coated with a conformal Cu layer and served as the electrode for CO 2 RR. The influence of several controllable structural parameters on the efficiency and selectivity of CO 2 RR was also investigated.…”
Section: Porous Microstructures Of Gdesmentioning
confidence: 99%